(untitled) (Journal of Pedagogical Inventions and Practices, 2023)
This article describes in detail the goals and tasks of pedagogical experimental work, the organization of educational activities based on a technological approach, the implementation of new pedagogical technologies in the educational process, the positive resolution of pedagogical tasks, the factors that ensure the effectiveness of educational activities by teachers of primary education classes.